The Difference in Criminal Defense and the Difference It Makes - Abbe Smith (Washington University Journal of Law & Policy, 2003)
No matter how weighty the civil case, it is different from a criminal case. This Essay examines this difference between civil and criminal cases, and the difference it makes in legal ethics.
Keywords: Defense attorneys; Defense (Civil procedure); Defense (Criminal procedure); Legal ethics; United States; Defence (Civil procedure); Defence (Criminal procedure)